Exploring emotional dimensions in educational data: A neutrosophic sentiment analysis approach - Joffre Paladines Rodríguez; Adrián del Pozo Biscarra; Felix Tamayo (Neutrosophic Sets and Systems)
This study contributes to the literature by trying to understand which emotions translate to transcription in the classroom from the perspective of emotional impact on academic achievement in digital environments. This is specific to the chosen sample population from Instituto Superior Tecnológico Guayaquil, which operates within the Google Classroom environment. The importance of such a study is essential in twenty-first-century life because relative emotions—positive or negative, from constructs like motivation, anxiety, or frustration—are integral to positioning and learning processes in digital teaching environments which excessively appear in today's higher education curriculum. Yet the state-of-the-art does not highlight such a systematic study of findings from digital environments; instead, it assesses classroom situations where researchers segment emotions into rigid categories. The unique approach here is neutrosophic sentiment analysis based on Smarandache's (1999) theory of trivalent logic which supports the ambiguity of emotional functioning. The findings reveal multiple emotions that facilitate and impede grades and participation in the classroom, as well as responsiveness and program complaints; therefore, signifying importance for cause and effect for digital environment use. Transferring educational theoretical application from this new field study to practical classroom situations through adjustable and fluid pedagogical teaching opportunities championing the use of digital environments for enhanced learning and student wellness.